Free living nematode communities as fundamental food for shrimps in the ecological - model of mangrove - shrimp farming ponds, Nam Can district, Ca Mau province - My Yen, Nguyen Thi; Thai, Tran Thanh; Duc, Nguyen Tan; Quang, Ngo Xuan (Vietnam Journal of Biotechnology, 2018)
Free-living nematodes were investigated in order to understand as the natural food for shirmp in the model of ecological mangrove – shirmp farm in mangroves forest according to their composition and densities by seasonal changes. Twenty – four samples of free living nematodes were collected in 8 ecological shrimp ponds (three replicate per pond) in 4 hamlets of Tam Giang commune, Nam Can district, Ca Mau province. Three sampling campaigns were carried out during dry, transitional and rainy seasons in year 2015. In total of 111 nematode genera, 32 families, 10 orders belong to 2 classes of free living nematodes were identified in these mangrove shrimp ponds. Nematode genera richness were quite high, and significant different among three sampling times while their density in the rainy season was considerably higher than such of the dry season. Some genera Pseudolella, Dichronema, Gomphionema, Ponponema, Halalaimus, Sphaerotheristus, Eumorpholaimus, Euleutherolaimus, Parodontophora, Ptycholaimellus, and Sabatieria were typical in these mangrove areas. Especially, two genera Daptonema and Terschellingia develop dominantly in 3 sampling campaigns. Additionally, a significant number of nematode genera were found in all sampling times whereas some other genera only represent in one season. Desities of nematode communities were recognised rather high. Average densities and standard deviation in each mangrove shrimp ponds ranged from 222 ± 122 (individual / 10 cm2) to 7255 ± 5454 (individual / 10 cm2). These characteristic of free living nematode communities in the ecological model of mangrove - shirmp ponds might provide suitable natural food source for shirmps and enrich the benthic foodweb.